(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
The article explores the stylistic role of qualifying syntactic constructions in the prose of A. I. Kuprin. Using the short story "The Garnet Bracelet" as an example, the author analyzes how the technique of qualification transforms an everyday detail into a profound psychological symbol. The study examines the functions of object-world detailing, the transmission of sensory experience, and the creation of the text’s emotional and rhythmic pattern, thereby justifying Kuprin’s status as a "poet of Russian prose."